Central bank liquidity during the financial market and economic crisis: observations, thoughts and questions - Pentti Pikkarainen (Bank of Finland, 2010)
The paper concentrates on illustrating and assessing central banks liquidity operations during the crisis that started in August 2007. In addition to the ECB, the central banks of Sweden, Switzerland, the United Kingdom, Australia, Japan, Canada and the United States are analyzed. During the crisis the liquidity operations of central banks have converged. In many cases, central bank balance sheets have undergone extremely strong growth. The actions by central banks raise a number of questions concerning exit from the measures taken, the impact of the measures, central banks risks and their governance structure
URN:NBN:fi:bof-20140807176
Keywords: 330